2016
DOI: 10.2147/dddt.s116192
|View full text |Cite
|
Sign up to set email alerts
|

Non-imidazole-based histamine H3 receptor antagonists with anticonvulsant activity in different seizure models in male adult rats

Abstract: A series of twelve novel non-imidazole-based ligands (3–14) was developed and evaluated for its in vitro binding properties at the human histamine H3 receptor (hH3R). The novel ligands were investigated for their in vivo protective effects in different seizure models in male adult rats. Among the H3R ligands (3–14) tested, ligand 14 showed significant and dose-dependent reduction in the duration of tonic hind limb extension in maximal electroshock (MES)-induced seizure model subsequent to acute systemic admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 67 publications
6
30
0
Order By: Relevance
“…A plethora of studies have related the heterogenic and complex pharmacology of histamine receptors to various diseases: H 1 R to the allergic inflammation, anaphylaxis, and motion sickness [28,29], H 2 R to the stimulation of gastric acid secretion leading to peptic ulcer, GERD and aspiration pneumonitis [30,31], H 3 R to the neurotransmission controlling sleep, cognitive processes, schizophrenia, epilepsy, and pain [32][33][34][35][36][37], and H 4 R to the immune responses (cancers, myocarditis) and inflammation [38][39][40][41][42] (Figure 2). The H 3 and H 4 receptors have relatively high affinity for histamine (5-10 nM) compared to the low affinity of H 1 R and H 2 R which is in the µM range [6,43].…”
Section: The Histamine Receptors-localization and Functionmentioning
confidence: 99%
“…A plethora of studies have related the heterogenic and complex pharmacology of histamine receptors to various diseases: H 1 R to the allergic inflammation, anaphylaxis, and motion sickness [28,29], H 2 R to the stimulation of gastric acid secretion leading to peptic ulcer, GERD and aspiration pneumonitis [30,31], H 3 R to the neurotransmission controlling sleep, cognitive processes, schizophrenia, epilepsy, and pain [32][33][34][35][36][37], and H 4 R to the immune responses (cancers, myocarditis) and inflammation [38][39][40][41][42] (Figure 2). The H 3 and H 4 receptors have relatively high affinity for histamine (5-10 nM) compared to the low affinity of H 1 R and H 2 R which is in the µM range [6,43].…”
Section: The Histamine Receptors-localization and Functionmentioning
confidence: 99%
“…Interestingly, in the past decades histamine H3 receptor (H3R) antagonists/ inverse agonists obtained an enormous attention regarding their possible diverse applications in the treatment of different neuropsychiatric diseases including epilepsy, dementia, Alzheimer's disease, autism spectrum disorder and cognitive impairment [16][17][18][19][20][21][22][23]. This owing to H3Rs unique feature by acting as autoreceptors through regulating the synthesis and release of histamine [24], in addition to acting as heteroreceptors by regulating the release of other neurotransmitters (e.g., acetylcholine, serotonin, noradrenalin and others) [23].…”
Section: Introductionmentioning
confidence: 99%
“…This owing to H3Rs unique feature by acting as autoreceptors through regulating the synthesis and release of histamine [24], in addition to acting as heteroreceptors by regulating the release of other neurotransmitters (e.g., acetylcholine, serotonin, noradrenalin and others) [23]. Moreover, other studies have indicated the protective effect of H3R antagonists/ inverse agonists in different acute seizures models including maximal electroshock (MES) and PTZ-induced seizure models [19,[25][26][27]. Furthermore, the procognitive effect of H3R antagonists/ inverse agonists was confirmed lately by applying different behavioral tests including inhibitory avoidance paradigm (IAP), novel object recognition test (NOR) and Morris water maze test (MWM) [20,26,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…In order to assess some central drug-safety properties for the selenium agents ( 1 – 8 and ebselen), and bearing in mind that certain inorganic-selenium compounds such as selenite (SeO 3 2− ) interact unfavourably with DNA, all relevant compounds were investigated for their possible mutagenic properties in vitro employing the microtiter Ames test [ 25 , 26 , 27 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%